Study on demographic variables of controlled ovarian Hyperstimulation and Intrauterine Insemination (husband) in a tertiary medical college and hospital in Kolkata - Sarkar, Agniv; Roy, Rajib; Chowdhury, Joydeb Roy; Dalal, Bibhas Saha (Asian Journal of Medical Sciences, 2021)
Background: Intrauterine Insemination (IUI) is anage old reliable and safe procedure for couples having infertility. Success rate of IUI with ovulation induction ranges from 8-20% depending on many factors. Aims and Objectives: The current study was to assess the factors which are responsible for favourable outcome of IUI after ovulation induction. Materials and Methods: Total 67 couples were included fulfilling inclusion and exclusion criteria. They underwent 90 cycles of IUI with each couple having maximum of 3 cycles. Ovulation induction was done byeitherclomiphene citrate or letrozole or gonadotrophins. Semen preparation was done by density gradient method. The participant’s demographic parameters were analyzed. Results: Out of 90 IUI, 8 were successful resulting in a success rate of 8.8% per cycle and 11.9% per couple. Factors which had positive impact were age less than 35 years, less than 10 years of infertility, normal and overweight BMI. Anovulation and unexplained infertility had better outcome. Type of infertility did not have any impact on the outcome. Conclusion: The study concluded that IUI after ovulation induction is more useful in cases like unexplained infertility and anovulation in a patient aged less than 35 years with less than 10 years of infertility and normal or overweight BMI.